Moderating effects of technological innovation and information environment on market response to information disclosure reforms - Danlei Feng; Lingdi Zhao (Heliyon)
Constructing an institutional environment centered around information disclosure (ID) is the direction of development for capital market reforms. This paper innovatively explores the stock market response (MR) to companies' enhanced ID due to institutional changes. Using data from Chinese companies listed on the Sci-Tech Innovation Board (STIB) from 2019 to 2023, the study employs Information Asymmetry Theory and Stakeholder Theory to analyze the relationship between ID levels and MR. The empirical analysis reveals a ''U-shaped'' relationship between ID level and MR. Furthermore, by introducing variables related to the information environment (IE) and technological innovation (TI), the study finds that their signaling effects vary among different audiences. High transparency in the IE and strong TI capabilities significantly mitigate the negative MR effects caused by revealing deficiencies during the enhancement of ID. This paper provides theoretical support and empirical evidence for capital market reform, improved financial regulation, enhanced credit quality of listed companies, and investor protection.